ANALISIS KEMAMPUAN LITERASI NUMERASI SISWA BERDASARKAN TEORI BELAJAR SIBERNETIK PADA MATERI SPLTV - Widyaningsih, Erika; Pujiastuti, Heni; Nandang Mustafa, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Numeracy literacy is the ability to solve everyday problems bay using mathematics to analyze information in the form of numbers, graphs, tables, and other formats, and to draw conclusions. According to the PISA report on mathematical literacy, Indonesia scored 366 out of average score of 476. This study aims to determine students’ numeracy literacy skill based on cybernetic learning theory regarding the SPLTV curriculum among 10th grade students at SMAN 14 Kabupaten Tangerang during the 2025/2026 academic year. The research subjects being students approach used in study is qualitative descriptive, with the research subject being students from classes X.9 and X.10 at SMAN 14 Kabupaten Tangerang using purposive sampling. Ini general, 10th grade students have an average numeracy literacy ability 29%. Most of them face difficulties in writing final answer and conclusions, as well in solving systems of linear equation with three variables. Thus, on average, 10th grade students are unable to meet the three indicators of numeracy literacy ability.